Towards a preschool music approach using environmental sound sources for non-musician teachers - Agustin, Estrella R. (2004)
This study utilized environmental sound sources as a medium for the different types of musical experiences. Children explored, described, interpreted, and organized environmental sound sources through their chanting, singing, making band playing child-made music instruments, rhythm patterns, an creative movement. This study is an attempt to develop a pre-school music approach for non-musician teachers. It went through a qualitative inquiry utilizing a multi-method of gathering data to answer the research questions. The main sources of data for this study were (1) video recording, (2) natural observation, (3) researcher's journal, (4) interview with the teacher respondent, and (5) sample works of children. After going through a cyclic analysis of data collected, the research questions were systematically answered. Two types of environmental sound sources can be utilized to introduce music concepts: extra -musical sounds and the intra-musical sounds. Music concepts such as timbre, dynamics, duration, tempo, pitch, and mood can be introduced by a non-musician teacher through process of sound exploration, discovering sound possibilities, listening and describing sounds, creating body movement that goes with the sound, creating musical instruments and playing sound sources to accompany songs, and creating simple rhythmic improvisations. There were five types of teacher-initiated changes done during the implementation of music experiences and there were omission, addition, substitutions, variation, and improvisation. The teacher-respondent employed different management styles to take control of the learning situations and these were (1) inserting 'on-the-spot' activity, (2) use of verbal phrases, (3) individualized attention, (4) process with the children to remind classroom rules. Music experiences become relevant when it is presented within the context of the child's experiences. This can be done by identifying curriculum themes and considering the interest and social cognition of the child. Music should not be treated as an isolated discipline or a special activity but it can be both a tool and a discipline. If music is treated as a separate subject, it must have the perspective of an integrated experience. While one can also derived music experiences from any curricular theme, the Integrated Core Curriculum of the University of the Philippines Child Development Center is an effective curriculum medium wherein music experiences can also be integrated.
Thesis (Ph.D. Educational Psychology)--University of the Philippines, Diliman.
Keywords: Preschool music -- Instruction and study -- Philippines -- Quezon City; Preschool music -- Instruction and study -- Activity programs -- Philippines -- Quezon City